A Typology of Stakeholders and Guidelines for Engagement in Transdisciplinary, Participatory Processes - Newton, Alice; Elliott, Michael (Frontiers in Marine Science, 2016)
This paper presents a typology of stakeholders for effective participatory processes and co-design of solutions to complex social-environmental issues and a roadmap stepwise methodology for balanced and productive stakeholder engagement. Definitions are given of terminology that is frequently used interchangeably such as “stakeholders”, “social actors” and “interested parties”. Eleven research questions about participative processes are addressed, based on more than 30 years of experience in water, estuarine, coastal and marine management. A stepwise roadmap, supported by illustrative tables based on case-studies, shows how a balanced stakeholder selection and real engagement maybe achieved. The paper brings these together in the context of several up-to-date concepts such as complex, nested governance, the 10 tenets for integrated, successful and sustainable marine management, the System Approach Framework and the evolution of DPSIR into DAPSI(W)R(M) framework. Examples given are based on the implementation of the Marine Strategy Framework Directive, the Water Framework Directive, the Environmental Impact Assessment Directive, the Framework for Marine Spatial Planning Directive, as well as for Regional Sea Conventions. The paper also shows how tools that have been developed in recent projects can be put to use to implement policy and maximize the effectiveness of stakeholder participation.